1996
DOI: 10.1021/bi960749f
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Flavin Semiquinone in the Resting State of Monoamine Oxidase B by Electron Paramagnetic Resonance and Electron Nuclear Double Resonance Spectroscopy,

Abstract: Monoamine oxidase (MAO) plays an essential role in the regulation of various neurotransmitter and xenobiotic amines. Inhibitors of MAO have been employed in the treatment of depression and as adjuncts in Parkinson's disease therapy. X-Band and Q-band electron paramagnetic resonance (EPR) and electron nuclear double resonance (ENDOR) spectroscopic techniques are employed to characterize a signal assigned as a stable red anionic semiquinone radical in the resting state of MAO B. It is shown that the radical sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
39
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 43 publications
9
39
2
Order By: Relevance
“…Further reduction by the addition of a total of 1.2 mol of dithionite per mole of enzyme results in the formation of the flavin hydroquinone, with little or no semiquinone form remaining (EPR data not shown). These data show that a semiquinone form is not required for enzyme activity as suggested by DeRose et al (21). This radical form in bovine liver MAO B probably originates from reactive oxygen species that are known to form on the disruption of mitochondria (45), although further work is required to document this suggestion.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Further reduction by the addition of a total of 1.2 mol of dithionite per mole of enzyme results in the formation of the flavin hydroquinone, with little or no semiquinone form remaining (EPR data not shown). These data show that a semiquinone form is not required for enzyme activity as suggested by DeRose et al (21). This radical form in bovine liver MAO B probably originates from reactive oxygen species that are known to form on the disruption of mitochondria (45), although further work is required to document this suggestion.…”
Section: Resultssupporting
confidence: 60%
“…The expressed enzyme exhibits many of the kinetic and structural properties of the well-studied bovine liver enzyme. The properties of the recombinant enzyme suggest the observed flavin radical in the resting form of the bovine enzyme observed previously (20,21) has no catalytic significance, in contrast to previous suggestions, and probably arises as an artifact of preparation. Using high-resolution mass spectral techniques, we found that the posttranslational modifications observed in bovine liver MAO B (N-terminal acetylation and covalent FAD incorporation) are also found in the recombinant human liver MAO B.…”
Section: Academic Presscontrasting
confidence: 60%
See 1 more Smart Citation
“…Previous EPR studies have not revealed the presence of the tyrosyl radical reported here (15,31). However, the conditions employed in these studies were not optimized for the detection of the additional features shown in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…An organic radical species was originally reported in EPR spectra of resting (i.e. flavin in the oxidized state) bovine liver MAO B [13,14], but more recent studies have confirmed the lack of a protein-based radical in highly purified forms of recombinant MAO A and MAO B in the resting state [15,16]. The lack of an observed radical species in the resting states of MAO A and MAO B therefore was seen to seriously question the validity of this proposed mechanism for the MAO enzymes.…”
mentioning
confidence: 99%